Biodegradation of anthracene and phenanthrene by bacteria isolated from oil-contaminated soil of Bangladesh. Issue 9 (21st October 2017) - Chowdhury, Rocky; Dhar, Kartik; Ahamed, Forkan; Alam, Shawkat; Uddin, Mohammad
ABSTRACT: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous environmental pollutants entering into the environment through natural and anthropogenic activities. Owing to their toxicity to various life forms including humans, detoxification of PAHs is crucial to reduce their effects on cells. In this study, we have isolated two bacteria capable of degrading two common PAHs, anthracene and phenanthrene, from contaminated soil samples by using selective enrichment culture supplemented with test PAHs as the sole source of carbon and energy. The isolated bacteria were identified and affiliated as Pseudomonas aeruginosa strain KD and Stenotrophomonas maltophilia strain RC based on their 16s rRNA gene sequences. The degradation of anthracene and phenanthrene was estimated indirectly by measuring the decolourisation extent of a redox indicator, 2, 6-dichlorophenolindophenol, incorporated into PAH-supplemented mineral salt media. In the case of anthracene, ≥90% decolourisation was recorded at 20 and 48 days for P. aeruginosa and S. Maltophilia, respectively. On the other hand, ≥94% decolourisation was recorded at 56 and 52 days for P. aeruginosa and S. maltophilia, respectively during the utilisation of phenanthrene.